A CREATIVE APPROACH TO FINANCIAL LITERACY IN PRIMARY SCHOOL STUDENTS - Yusupova Shakhzoda Yunus kizi; Tashmatova Shalola Ravshanbekovna (Scholar Express Journal, 2022)
This article discusses creative approach and different methods of developing financial literacy in younger students, and also combines creativity with innovative methods to describe productivity and interest in the problem under study.
Keywords: Education; Primary School; Creative; Financial Literacy